Pengaruh City Image Dan City Branding Terhadap Minat Berkunjung Ke Destinasi Wisata Lokal Di Kota Batu (Studi Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2017 ) - Solikin Solikin; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstrak This study aims to determine the effect of City Image and City Branding on interest in visiting local tourist destinations in Batu city. This research is a type of explanatory research. The research subjects were 70 students of FEB Malang Islamic University class of 2017. The method of data collection is done by using a questionnaire. The analysis method used is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, determination coefficient test, and hypothesis test. The results showed that City Image and City Branding have an effect on the interest in visiting local tourist destinations in Batu City, simultaneously City Image and City Branding on the Interest in Visiting Local Tourist Destinations in Batu City on Students of the Faculty of Economics and Business Malang Islamic University Class of 2017, the influence partially City Image and City Branding on the Interest of Visiting Local Tourist Destinations in Batu City for Students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2017. Keywords: City Image, City Branding, Interest in visiting